BENTUK PENYAJIANTALEMPONG SIKATUNTUANG DALAM ALEK BARARAK ANAK DARO DAN MARAPULAI DI KELURAHAN PADANG ALAI PAYAKUMBUH TIMUR - Nova Rita Satria; Wimbrayardi Wimbrayardi; Marzam Marzam (SENDRATASIK UNP, 2013)
Abstract   This Research aims at describing the presentation of Talempong Sikatuntuang in Bararak alek anak daro and marapulai (bride and groom procession) in Subdistrict of Padang Alai of East Payakumbuh. This qualitative research used descriptive method in the research analysis. The Talempong Sikatuntuang in wedding ceremony is performed in form pageant which is played in ensemble music. The performance only presents talempong which is played in the time of  anak daro and marapulai (bride and groom) and the family of his father start the parade from the bride’s house to the groom’s house. Sikatuntuang is also played in the time of both the bride and groom arrive at the groom’s house.   Key word : Talempong Sikatuntuang, Pesta Perkawinan, Kualitatif.